In vitro and in vivo lipolysis of plasma triglycerides increases the resistance to oxidative modification of low-density lipoproteins. - Skoglund-Andersson, C; Karpe, F; Hellénius, M; Regnström, J; Hamsten, A; Tornvall, P (2003)
BACKGROUND: The majority of studies on low-density lipoprotein (LDL) particle size and susceptibility to oxidative modification have been either descriptive or interventional, but there are few mechanistic studies. MATERIALS AND METHODS: Effects of exhaustive in vitro and in vivo lipolysis of serum and plasma triglycerides, respectively, by lipoprotein lipase (LPL) were investigated in healthy normotriglyceridemic men. The LDL end-product of lipolysis of very low-density lipoprotein (VLDL) underwent compositional analysis, gradient gel electrophoresis and an assessment of resistance to copper-induced oxidative modification. RESULTS: The LDL particle contents of free fatty acid and alpha-tocopherol increased, whereas the contents of free and esterified cholesterol, alpha-carotene and coenzyme Q10 decreased upon incubation of serum with LPL in vitro. The LDL particle size decreased and the resistance to the oxidative modification of LDL increased. Lipolysis of plasma triglycerides in vivo, achieved by intravenous injection of heparin, did not alter the LDL particle size but increased the resistance to the oxidative modification of LDL. This change was accompanied by an increase in the LDL particle content of alpha-tocopherol, whereas the free fatty acid content was unaltered. CONCLUSIONS: The results show that the increased resistance to oxidative modification of LDL after lipolysis of plasma triglycerides was concomitant with an increased LDL particle content of alpha-tocopherol, and that free fatty acids did not seem to contribute to the increased resistance to oxidative modification of LDL in vivo. Furthermore, our data indicate that the resistance of LDL to oxidative modification is not dependent on particle size.